Three Firmans From the First Half of 19th Century - Hadžibegić, Hamid (Prilozi za orijentalnu filologiju, 2017)
This paper presents three firmans (Sultan's edicts) dating from the time of S leyman the Legislator's rule and they refer to the region of Macedonia. The first of them dates from 939 (1532-3) and refers to Yuruks (members of the yenicery accessory army). lt was issued after the complaint of a spahi from the Štip kadiluk against illegal acts done by the yuruks. The Sultan's firman states precisely the rights and obligations of cattle-breeders and those who cultivated raya's land. The Ćustendil sanjakbey and the Štip quadi were ordered to consider this case and to procede according to the mentioned legal regulations. The second firman was addressed to the Ćustendil sanjakbey and the Štip quadi. The Sultan ordered by this firman that all conflicts should be solved at places teritorially authorized for them. It was forbidden to the sanjakbey to call people involved in conflicts to his place and toquestion them or to send them to a quadi who was not teritorialy authorized for a certain dispute. The third firman deals with injustice and violence in the Solun sanjak done by those who collected harač and sheep-tax or by those who were coming because of oarsmen or other suchlike jobs. In connection with this the sanjakbey and the quadi were ordered to prevent such injustices and violence.